2022
DOI: 10.4018/ijssmet.315592
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Securitization as a Yardstick for Investment in Islamic Capital Markets

Abstract: The paper shows that Islamic securitization through Sukuk securities is vital in fostering the Islamic capital market. Sukuk investments entail investors and issuers to follow a set of nuanced moral and ethical principles beyond maximizing profit. As measured by social trust, investor trust could be critical in the worldwide Sukuk investment boom. Therefore, the primary objective of the article is to demonstrate the impact of Islamic securitization through the Sukuk bonds in guaranteeing investment in the Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It is due to the distinction between two that the study confirmed that it is paramount to develop Islamic financial system based on the framework of the objective of Shari'ah. In so doing, Islamic securitization is the yardstick for investment in capital markets (Hassan et al, 2022). Moreso, socio-economic injustice is a grieve impediment to the societal progress and addressing this problem is the core aspect of Islamic economic and financial system.…”
Section: Discussionmentioning
confidence: 99%
“…It is due to the distinction between two that the study confirmed that it is paramount to develop Islamic financial system based on the framework of the objective of Shari'ah. In so doing, Islamic securitization is the yardstick for investment in capital markets (Hassan et al, 2022). Moreso, socio-economic injustice is a grieve impediment to the societal progress and addressing this problem is the core aspect of Islamic economic and financial system.…”
Section: Discussionmentioning
confidence: 99%
“…The domain of Islamic capital market literacy is characterized by a narrower focus, wherein the norms and provisions governing the capital market are rooted in Sharia or Islamic principles. This entails adherence to Islamic rules in all aspects of the market's operations, including the activities of issuers, the types of securities traded, and the mechanisms employed for trading (Hassan & Mehar, 2022). The conclusion that can be drawn is that Islamic capital market literacy refers to the acquisition of knowledge and skills pertaining to the capital market, specifically in accordance with Islamic principles, with the aim of generating advantages and promoting well-being.…”
Section: Islamic Capital Market Literacymentioning
confidence: 99%
“…As previously said, the field of Islamic capital market literacy exhibits a more limited scope, with its emphasis on the regulations and principles derived from Sharia or Islamic teachings that govern the capital market. The strict observance of Sharia principles in every facet of the market's functioning, encompassing the conduct of issuers, the kind of assets exchanged, and the trading instruments deployed, is deemed mandatory (Hassan & Mehar, 2022). These conditions will impact the perceived risk by investors.…”
Section: Risk Perceptionmentioning
confidence: 99%
“…Depending on the strength of their backing, both bonds and sukuk can be ranked by rating authorities. There are also similar differences in the design and issuers of bonds and sukuk, giving consumers arrange of options when considering these instruments (Hassan et al, 2022).…”
Section: And Findingsmentioning
confidence: 99%